COHERENCE AND COHESION IN ACADEMIC CONTEXT - Sadullayeva , Nozima (Scientific practical conference, 2026)
Academic writing is a kind of formal style of writing practiced mainly in the universities and in publications. Cohesion and coherence, which refer to intra-text connectedness, and the contextual fitness of the ideas, are the essential properties of the texts in academic writing so as to create them (the texts) more comprehensible. This article makes an attempt to acquaint the readers with academic writing; and introduce cohesion and coherence, which add quality in the standard of textuality in academic writing.